Inovasi Pembelajaran Sosial Emosional Melalui Regulasi Emosi - Hamdani, Cindy Gusvita (LPPI Yayasan Almahmudi bin Dahlan, 2026)
This research explores the importance of integrating Social Emotional Learning (SEL) into primary education through the reflective practices of pre-service teachers within the Teacher Professional Education Program (PPG). The primary focus of this study is to analyze how the application of emotional regulation strategies can create a conducive learning atmosphere and improve the quality of students' character holistically. The research method employed is library research, examining the CASEL concepts and their practical implementation in mathematics learning for fourth-grade elementary school students. The discussion results indicate that structured social-emotional learning, executed with a contextual approach, serves as a significant innovation in enhancing educational quality. The use of innovative techniques such as the